Pengaruh Proyek Drama Musikal Terhadap Penguatan Profil Pelajar Pancasila - Rochmania, Desty Dwi; Salamah, Evi Rizqi; Pratiwi, Emy Yunita Rahma; Susilo, Claudya Zahrani; Laksono, Yunanto Tri; Basir, Udjang Pairin M. (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2024)
This research aims to determine the influence of the musical drama project on strengthening the Pancasila student profile of students at SDN Jombatan 3 Jombang. The research method used in this research is an ex post facto method with a quantitative approach. The subjects of this research were students at SDN Jombatan 3 Jombang. The sample in this study consisted of 32 students who were the population sample. The data calculation technique uses SPSS version 21. The results of this research can be concluded that there is a significant influence of the musical drama project on strengthening the profile of Pancasila students. Where the significant value of tcount (5% = 170.592) is greater than ttable (0.361) and at the 0.000 significance level it is less than 0.05 so it can be concluded that in the research the alternative hypothesis Ha is accepted and Ho is rejected. This means that there is a very big influence from the musical drama project on strengthening the Pancasila student profile for students at SDN Jombatan 3 Jombang, seen from the calculation of the coefficient of determination value of 85% of this influence. Implementing the Strengthening Pancasila Student Profile Project certainly requires cooperation between students. In this case, it is clear that the character of mutual cooperation and creativity are two important characters in working on a Project for Strengthening the Profile of Pancasila Students. The Pancasila Student Profile Strengthening Project is expected to inspire students to contribute to the surrounding environment. It is also hoped that the Strengthening Pancasila Student Profile Project can be an optimal means of encouraging students to become lifelong learners who are competent, have character and behave in accordance with Pancasila values.